Effectiveness of transnational adaptation initiatives in the Global South - Kirr, Julia Sophia (Department of Environmental and Geographical Science, 2022)
Current efforts from national governments in the fight against global warming are insufficient and studies suggest that reaching the agreed 1.5°C target is unlikely with existing pledges and targets. Transnational climate change governance (TCCG) has become increasingly pervasive and gained significant political, economic and environmental influence over the past years. However, such efforts are still dominated by actors from the Global North and have for a long time predominantly focused on mitigation. Furthermore, little insights exist into how certain factors are beneficial or detrimental to the success of TCCG. This study assesses the effectiveness of 17 transnational adaptation initiatives in the Global South and investigates how various factors contribute to or hinder the achievement of set goals. Based on documentary analysis and primary interview data, the effectiveness of the initiatives was measured on a three-point scale and crucial aspects with regards to actors, process design and meta-governance were identified. The study finds a strong bias towards coordinating actors from the Global North. Furthermore, stark asymmetries exist in information, resources, interests and power, especially between the North and South, which hinder the achievement of goals. A high level of institutionalization and strong internal organization were identified as beneficial for the effectiveness of transnational adaptation initiatives. In contrast to that, a lack of robust monitoring and evaluation (M&E) systems as well as insufficient funding significantly impede goal achievement. Adequate M&E is hampered by lack of standardization as well as low commitment and buy-in from stakeholders, while lack of funding can become problematic if initiatives are too dependent on one donor and an end to funding threatens the sustainability of a programme. Lastly, alignment with and conduciveness to international regimes and related frameworks as well as collaboration with other initiatives can be beneficial. The study concludes that it is important to strengthen the capacities of actors from the Global South in order to enable them to take over coordinating roles. Furthermore, transnational adaptation initiatives are recommended to invest into institutionalization and establishing good governance structures such as a secretariat with full-time staff and steering committee, as well as management measures. A robust M&E system is required that goes beyond the output level and is well communicated to all stakeholders. Multiple funding sources should be considered in order to avoid too much dependency on one donor and international frameworks should be used and transferred to local levels. Lastly, initiatives are recommended to keep a high level of flexibility in their operations and adapt to the local context.